Weakly closed multifunctions and paracompactness - Cao Ji-Ling (International Journal of Mathematics and Mathematical Sciences)
The purpose of the present paper is to investigate weakly closed multifunctions between topological spaces. We discuss basic properties of weakly closed multifunctions and some results of Rose and Janković are extended. Our main theorems are concerning some properties of paracompactness under weakly closed multifunctions. These theorems are generalizations of some results due to Kovaćević and Singal.